Pelatihan Pengelolaan Keuangan pada Pokdakan Farm Estate Martubung - Rajagukguk, Ronald Hasudungan; Sinaga, Annisa Nauli; Sitanggang, Tina Novianti; Benget P, Jhon Lismart; Riadi, Riadi (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
Financial management is a crucial yet often overlooked aspect in the operations of micro-scale fish farmer groups. Pokdakan Farm Estate Martubung, located in the Martubung residential area, faces constraints in financial administration due to a limited understanding of basic accounting, resulting in the absence of clear financial reports to evaluate business profitability. This community service activity aims to improve the knowledge and skills of group members in managing business finances, ranging from recording daily transactions to preparing simple financial statements. The method used is participatory community empowerment through stages of socialization, intensive training (workshops), and field mentoring. The results of the activity indicate a significant increase in participants' motivation and managerial awareness. Although the majority of participants do not have an accounting education background, they were able to understand and practice journalizing and preparing income statements after being provided with real-case-based simulations. The group now possesses formal recording documents as tools for business transparency and evaluation. This program concludes that managerial intervention is highly effective in shifting the mindset of traditional farmers into more professional business managers. It is recommended that there be continuous assistance from the local government and related institutions to ensure the sustainability of the established administrative system so that Pokdakan Farm Estate Martubung can develop into an independent and competitive business unit.